Kritik Sosial dalam Novel Pasung Jiwa Karya Okky Madasari (Social Criticism in the Novel Pasung Jiwa by Okky Madasari) - Lusy Novitasari (Indonesian Language Education and Literature, 2021)
This study aims to describe and explain the social criticism contained in the novel Pasung Jiwa by Okky Madasari. The method used is the descriptive qualitative method. The data source of this research is the text of the novel Pasung Jiwa by Okky Madasari, first printed in 2013 and published by PT Gramedia Pustaka Utama Jakarta Publisher. This research is focused on problems related to social criticism. The data was obtained by using the document technique and analyzed in terms of content. The approach used in the sociology of literature. The research stages consist of data identification, data description, data analysis, and data interpretation. The results of the study indicate that this novel contains criticisms of parental/family confinement, abuse of transgender women, the miserable life of factory workers, the lives of commercial sex workers, those in power, and government arbitrariness, as well as the existence of laskar/religious defenders.Penelitian ini bertujuan untuk mendeskripsikan dan menjelaskan kritik sosial yang terdapat dalam novel Pasung Jiwa karya Okky Madasari. Metode yang digunakan adalah metode deskriptif kualitatif. Sumber data penelitian ini adalah teks novel Pasung Jiwa karya Okky Madasari, cetakan pertama tahun 2013 dan diterbitkan oleh Penerbit PT Gramedia Pustaka Utama Jakarta. Penelitian ini difokuskan pada permasalahan yang berkaitan dengan kritik sosial. Data diperoleh dengan menggunakan teknik dokumen dan dianalisis dari segi isi. Pendekatan yang dipergunakan adalah sosiologi sastra. Tahapan penelitian terdiri atas: identifikasi data, deskripsi data, analisis data, dan interpretasi data. Hasil penelitian menunjukkan bahwa novel ini mengandung kritik terhadap: kungkungan orang tua/keluarga, kesewenangan kepada waria (transgender), kehidupan nestapa buruh pabrik, kehidupan pekerja seks komersial, pihak yang berkuasa dan kesewenangan pemerintah, serta adanya laskar/pasukan pembela agama.